Phase‐Controlled Deposition of Copper Sulfide Thin Films by Using Single‐Molecular Precursors. Issue 3 (4th December 2013) - Ashraf, Saba; Saeed, Aamer; Malik, Mohammad Azad; Flörke, Ulrich; Bolte, Michael; Haider, Naghmah; Akhtar, Javeed
Abstract: Herein, we describe the synthesis and characterization of new ligands, N, N ‐diethyl‐ N′ ‐(1‐naphthoyl)thiourea (1a ) and N, N ‐dipropyl‐ N′ ‐(1‐naphthoyl)thiourea (1b ), and their complexes with copper, bis[ N, N ‐diethyl‐ N′ ‐(1‐naphthoyl)thioureato]Cu II (2a ) and bis[ N, N ‐dipropyl‐ N′ ‐(1‐naphthoyl)thioureato]Cu II (2b ). All four compounds (i.e., 1a, 1b, 2a, and2b ) were characterized by elemental analysis, 1 H NMR and 13 C NMR spectroscopy, and FTIR spectroscopy. The structures of compounds1a, 1b, and2b were determined by single‐crystal X‐ray diffraction analysis. Thermogravimetric analysis of2a and2b showed that both compounds decompose between 190 and 370 °C. Compounds2a and2b were then used as single‐molecular precursors for the deposition of copper sulfide thin films through aerosol‐assisted chemical vapor deposition. The phase and purity of the as‐deposited thin films were confirmed by powdered X‐ray diffraction, which showed that the as‐grown films were composed of the orthorhombic (Cu7 S4 ) phase only. Morphological studies of the as‐deposited films were performed by using field‐emission scanning electron microscopy. The elemental composition of the thin films was determined by energy‐dispersive X‐ray spectroscopy. Abstract : Phase‐controlled deposition of thin films of copper sulfide on a glass substrate is achieved for the first time by using single‐molecular precursors through aerosol‐assisted chemical vapor deposition. The as‐deposited thin films are characterized by field‐emission scanning electron microscopy, powdered X‐ray diffraction, and energy‐dispersive X‐ray spectroscopy.